2021
DOI: 10.3389/fmed.2021.720128
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering CHFR Role in Pancreatic Ductal Adenocarcinoma

Abstract: Checkpoint with forkhead-associated and ring finger domains (CHFR) has been proposed as a predictive and prognosis biomarker for different tumor types, but its role in pancreatic ductal adenocarcinoma (PDAC) remains unknown. The aim of this study was two-pronged: to review the role of CHFR in PDAC and evaluating CHFR as a potential predictive biomarker in this disease. For this purpose, we first explored the CHFR messenger (m)RNA expression and promoter methylation through the TCGA database. Secondly, the CHFR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…This strategy has been useful in identifying regulatory SNPs associated with PDAC susceptibility that have been overlooked by the original GWASs 11 24 25. In addition to genetics, several studies have also identified a relevant role of epigenetics in PDAC aetiology, and in particular in the deregulation of DNA methylation, with hypermethylation of tumour suppressor genes and hypomethylation of oncogenes 26–28. However, DNA methylation shows variability across a lifetime, in response to environmental stimuli or ageing, and shows tissue specificity,29 making the studies that rely on blood as a proxy tissue difficult to interpret with respect to the methylation in a specific organ 30.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy has been useful in identifying regulatory SNPs associated with PDAC susceptibility that have been overlooked by the original GWASs 11 24 25. In addition to genetics, several studies have also identified a relevant role of epigenetics in PDAC aetiology, and in particular in the deregulation of DNA methylation, with hypermethylation of tumour suppressor genes and hypomethylation of oncogenes 26–28. However, DNA methylation shows variability across a lifetime, in response to environmental stimuli or ageing, and shows tissue specificity,29 making the studies that rely on blood as a proxy tissue difficult to interpret with respect to the methylation in a specific organ 30.…”
Section: Introductionmentioning
confidence: 99%